STUDY OF THE MECHANISM OF VOLTAGE GENERATION IN THE ORDER OF 12-24 V POTENTIAL BY MEANS OF THERMO EMF BASED ON THE SEEBECK EFFECT (American Journal of Technology and Applied Sciences, 2025)
This article studies the mechanism of generating potential difference in the range of 12-24 V DC using the thermoelectromotive force arising at the boundary of two dissimilar conductors. The experimental conditions are considered, including the choice of materials, temperature conditions, the influence of the conductor cross-section, and the use of transformers to increase the output voltage. An analysis of the feasibility of this economic approach is carried out, taking into account some costs.